PERCEPATAN MENGHAFAL AL-QUR’AN MELALUI PEMBELAJARAN KOSA KATA BAHASA ARAB - Amirul Mukminin (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2020)
Basically, the general obstacle or problem in memorizing al-Qur'an in Indonesia is about the language of the Qur'an which is a foreign language for memorizers in Indonesia. Which is the language of the Tahfidz al-Qur'an is the latest innovation in MTs SA ALHIDAYAH Batu-Malang City. To applicate this program was greatly helped by the existence of Arabic learning that had taken place before the Tahfidz program. So that, with the collaboration of learning Arabic and tahfidz, students feel helped and fast in memorizing. The one of methods used in learning Arabic that help with the tahfidz program is Arabic vocabulary memorization system and its meanings as much as possible.